Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3168/jds.2018-15241
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Vitamin D status and responses in dairy cows naturally infected with Mycobacterium avium ssp. paratuberculosis

Abstract: Serum samples were obtained from Holstein dairy control cows and cows naturally infected with Mycobacterium avium ssp. paratuberculosis (MAP) to evaluate the effects of disease status on serum 25-hydroxyvitamin D 3 (25OHD 3 ) levels. Disease status was stratified for infected cows into asymptomatic, subclinical infection (n = 25), and cows demonstrating clinical signs (n = 20), along with noninfected control (n = 12) cows for comparison. In addition, portions of the ileocecal valve were taken from a subsample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In agreement with these findings, recent reports have demonstrated that MAP is able to manipulate the host lipid metabolism and accumulate cholesterol within macrophages which might favor MAP persistence 49 . In addition, decreases in serum 25-hydroxyvitamin D 3 (25OHD 3 ) levels were significantly lower in cows in the clinical stage of disease compared with either cows in the subclinical stage and non-infected control cows 50 . It is generally accepted that cattle in advanced stages of MAP infection are unable to metabolize and absorb vitamin D 3 across the intestinal wall, and therefore suffer from weight loss and cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these findings, recent reports have demonstrated that MAP is able to manipulate the host lipid metabolism and accumulate cholesterol within macrophages which might favor MAP persistence 49 . In addition, decreases in serum 25-hydroxyvitamin D 3 (25OHD 3 ) levels were significantly lower in cows in the clinical stage of disease compared with either cows in the subclinical stage and non-infected control cows 50 . It is generally accepted that cattle in advanced stages of MAP infection are unable to metabolize and absorb vitamin D 3 across the intestinal wall, and therefore suffer from weight loss and cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Little work has been done characterizing links between vitamin D 3 status and vitamin D 3 treatment on immune responses from cattle infected with MAP. Cows in the clinical stage of infection have been previously reported to have significantly reduced serum 25(OH)D 3 levels, possibly due to inhibition of dietary vitamin D 3 absorption from pathologic intestinal mucosal thickening ( Stabel et al., 2019 ; Wherry et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Infected animals were naturally infected with MAP and were classified into the subclinical and clinical categories based upon fecal shedding, determined by fecal culture and PCR, and clinical signs [18]. Infected and control cows were housed separately at the NADC and tested at least biannually, with endpoint testing just prior to necropsy [19]. Cows were housed in the dairy cattle barn onsite with access to freestall and pasture areas for resting.…”
Section: Methodsmentioning
confidence: 99%